Pengaruh Metode Eksperimen Menggunakan Model Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa Pada Materi Larutan Elektrolit dan Non Elektrolit - Justitia Mifthania Bulotio; Ni Wayan Suriani; Rymond Rumampuk (Chemistry Department, Universitas Negeri Manado, 2020)
This research is limited to the pronlem of the effect of experimental method using the problem based learning model which aims to find out wheather there is an effect of the experimental method using the problem based learning model on the average student learning outcomes on electrolyte and non elsctrolyte solution. This research is the experimental research conducted in X class of MIA MAN 1 Bitung in the academic year 2019/2020, and uses two classes namely class X MIA 1 as an experimental class and class X MIA 2 as an control class. The results of research in the experimental class given the experimental method used the problem based learning model obtained an averaged value of 89,2 while for the control class that was only given the experimental method obtained an averaged value of 50,6. For testing the hypothesis obtained thad H1 is accepted so it can be stated that the average student learning outcomes applied by the experimental method used the problem based learning model are higher than those using only the experimental method